Peran Pemeriksaan Rutin Penyakit Sindrom Metabolik dalam Upaya Mengurangi Risiko Kerapuhan dengan Pemeriksaan Frail pada Kelompok Usia Lanjut - Noer Saelan Tadjudin; Muhammad Kharis Mahdaviqa; Kresna Bambang Fajarivaldi; Edwin Destra (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
Metabolic syndrome, encompassing hypertension, elevated blood glucose levels, high cholesterol, and increased waist circumference, is a significant risk factor for frailty in older adults. The FRAIL questionnaire is a screening tool that assesses five components of frailty, enabling early detection for appropriate intervention. This community service program was conducted using the PDCA (Plan-Do-Check-Act) method with 93 elderly participants. Health education and screening for metabolic syndrome and frailty were performed using the FRAIL questionnaire. Among the participants, 22.58% were categorized as "Non-Frail," 50.54% as "Pre-Frail," and 26.88% as "Frail." These findings indicate a high prevalence of frailty risk among the elderly population. The FRAIL questionnaire proved effective for early detection of frailty, facilitating preventive interventions such as physical activity, nutritional monitoring, comorbidity management, and psychosocial support. These measures have the potential to sustain long-term health in older adults. The application of the FRAIL questionnaire for the elderly provides significant benefits for managing frailty risk, with a sustainable approach that promotes the well-being of older adults.